2021
DOI: 10.3390/plants11010049
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Plant Growth-Promoting Ability of Endophytic, Halotolerant Bacteria Associated with Tetragonia tetragonioides (Pall.) Kuntze

Abstract: The diversity of salt-tolerant cultivable endophytic bacteria associated with the halophyte New Zealand spinach (Tetragonia tetragonioides (Pall.) Kuntze) was studied, and their plant beneficial properties were evaluated. The bacteria isolated from leaves and roots belonged to Agrobacterium, Stenotrophomonas, Bacillus, Brevibacterium, Pseudomonas, Streptomyces, Pseudarthrobacter, Raoultella, Curtobacterium, and Pantoea. Isolates exhibited plant growth-promoting traits, including the production of a phytohormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Inoculation of fenugreek plants with P. endophytica SK1 enhanced P content in both control and salt-stressed plants. Similar observations of increase in P uptake in plants through co-inoculation with phosphate-solubilizing bacteria has been reported earlier (Egamberdieva et al, 2022;Kumar et al, 2020;Shurigin et al, 2022). P. endophytica SK1, in the present study, was able to solubilize phosphate enabling more P uptake in fenugreek plant under salt stress.…”
Section: Discussionsupporting
confidence: 92%
“…Inoculation of fenugreek plants with P. endophytica SK1 enhanced P content in both control and salt-stressed plants. Similar observations of increase in P uptake in plants through co-inoculation with phosphate-solubilizing bacteria has been reported earlier (Egamberdieva et al, 2022;Kumar et al, 2020;Shurigin et al, 2022). P. endophytica SK1, in the present study, was able to solubilize phosphate enabling more P uptake in fenugreek plant under salt stress.…”
Section: Discussionsupporting
confidence: 92%
“…When plants grow in severe salinity and drought environments, the presence of endophytic bacteria in these plants may help them to survive and grow in these conditions. Several studies have shown the beneficial effects of endophytic bacteria on their host plants, such as the Salicornia brachiate [ 21 ] plant, Cicer arietinum [ 22 ], Haloxylon ammodendron [ 23 ], Nypa fruticans [ 24 ], Salicornia bigelovii [ 25 ], Armoracia rusticana [ 26 ], Seidlitzia rosmarinus [ 27 ], Calendula officinalis [ 28 ], Halocnemum strobilaceum [ 29 ], Haloxylon aphyllum [ 30 ], Tetragonia tetragonioides [ 31 ], and other plants. In this study, we have isolated an endophytic bacterium from the salt marsh halophyte, Bolboschoenus planiculmis .…”
Section: Introductionmentioning
confidence: 99%
“…Like other identified Stenotrophomonas species, S. maltophilia is a Gram-negative, rod-like, spore former, and facultative anaerobe, that is commonly found in a plant-soil environment. Recent findings on some agriculturally important Stenotrophomonas species are evident in literature, which suggests their future exploration as a suitable candidate in the formulation of bioinoculants to provide for a stable ecosystem, provide biosafety, and create sustainable agriculture (Alexander et al 2019;Ulrich et al 2021;Egamberdieva et al 2022).…”
mentioning
confidence: 99%